The Effect of Awareness and Knowledge on Taxpayer Compliance in Paying Building Land Tax - Priantono, Seger; Fajariana, Dewi Endah; Qoyyimah, Amelia Nurdini (Politeknik Negeri Bengkalis, 2023)
The research was conducted in Maron Village, Probolinggo Regency with the aim to test the effect of taxpayer awareness on taxpayer compliance to pay land and building tax, and to test the effect of taxpayer knowledge on taxpayer compliance to pay land and building tax. The type of research used is quantitative descriptive with a causal associative approach. Data sources in the form of primary data were collected using questionnaires measured on a Likert scale, this study used a sample of 394 land and building tax taxpayers in Maron Village. Descriptive analysis methods and statistical analysis are used in the form of Partial Least Square (PLS) analysis data, namely outer model analysis, inner model analysis, and hypothesis testing. The results showed that awareness has a significant effect on taxpayer compliance to pay land and building tax in Maron Village, Probolinggo Regency, and knowledge has a significant effect on taxpayer compliance to pay land and building tax in Maron Village, Probolinggo Regency